A mother's courage [videorecording (DVD)] : talking back to autism - Friðrik Þór Friðriksson; Winslet, Kate (First Run Features, 2010)
Follow one woman's journey as she tries to help her severely autistic son break out of his own mind. Traveling to the United States from her home in Iceland to try to learn more about this complex condition, she meets along the way other families who have similar situations and all are looking for some answers.